2022
DOI: 10.3390/su14063406
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Distance Intervals on Walking Likelihood in Different Trip Purposes

Abstract: Increasing private car ownership and car dependency has led to a low share of walking as an active mode as well as congestion, air pollution, and health problems in developing countries. This paper aims to identify and compare the impacts of a selection of socio-economic, travel-related, and built environment variables on walking likelihood and respondents’ sensitivity to the walking distance, both for discretionary and mandatory trips. The analysis drew its origin from 14,463 responses acquired through an ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The majority of the research highlighted the importance of the built environment on pedestrian behaviors [28][29][30]. Distance also affects the pedestrian behaviors [26,31]. To consider LU diversity, population density, commercial density, and intersection density in research, Peiravian et al introduced a pedestrian environment index [32].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the research highlighted the importance of the built environment on pedestrian behaviors [28][29][30]. Distance also affects the pedestrian behaviors [26,31]. To consider LU diversity, population density, commercial density, and intersection density in research, Peiravian et al introduced a pedestrian environment index [32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Discretionary walking, which refers to walking trips undertaken for leisure, recreational, or non-essential purposes, has emerged as a focal point in transportation research [27]. This trend has been observed in recent studies such as those conducted by Macioszek et al, which underscores the importance of understanding and promoting discretionary walking within urban environments [31]. Regarding the aforementioned importance of discretionary trips, limited studies have demonstrated the influence factors that influence these trips.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides travel-related characteristics, it was found that individual characteristics and attitudes significantly affect travel mode choice. Variables such as age, gender, car ownership and income are often considered as influential variables on people's choices (Chatterjee, 2011;Mackett & Sutcliffe, 2003;Popuri et al, 2011;Macioszek et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, contradictory findings highlight the need for a more comprehensive examination of travel behavior, preference for transit, and private car users' shift to SAVs. In addition, a precise study of individuals' preferences and attitudes is widely recognized as being essential for the successful implementation of any policy [25].…”
Section: Introductionmentioning
confidence: 99%